Computing Metal‐Binding Proteins for Therapeutic Benefit. (29th April 2021) - Spinello, Angelo; Borišek, Jure; Pavlin, Matic; Janoš, Pavel; Magistrato, Alessandra
Abstract: Over one third of biomolecules rely on metal ions to exert their cellular functions. Metal ions can play a structural role by stabilizing the structure of biomolecules, a functional role by promoting a wide variety of biochemical reactions, and a regulatory role by acting as messengers upon binding to proteins regulating cellular metal‐homeostasis. These diverse roles in biology ascribe critical implications to metal‐binding proteins in the onset of many diseases. Hence, it is of utmost importance to exhaustively unlock the different mechanistic facets of metal‐binding proteins and to harness this knowledge to rationally devise novel therapeutic strategies to prevent or cure pathological states associated with metal‐dependent cellular dysfunctions. In this compendium, we illustrate how the use of a computational arsenal based on docking, classical, and quantum‐classical molecular dynamics simulations can contribute to extricate the minutiae of the catalytic, transport, and inhibition mechanisms of metal‐binding proteins at the atomic level. This knowledge represents a fertile ground and an essential prerequisite for selectively targeting metal‐binding proteins with small‐molecule inhibitors aiming to (i) abrogate deregulated metal‐dependent (mis)functions or (ii) leverage metal‐dyshomeostasis to selectively trigger harmful cells death. Abstract : Metal ions play fundamental structural, functional, and regulatory roles in biomolecules. In this compendium, we exemplify how all‐atom simulations have contributed to unravel the mechanistic facets underlying catalysis, transport, and inhibition of metal‐binding proteins. Harnessing this knowledge is essential to successfully develop selective small‐molecules inhibitors to improve human health condition.